Pembelajaran Fonetik Bahasa Indonesia Pada Mahasiswa Asal Sunda - Eca Wulandari; Hilpi Hilpia; Anisa Rahma (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research focuses on improving Indonesian pronunciation for Sundanese students who speak Sundanese. The learning method includes teaching pronunciation with material reading and writing phonetic symbols. Observation is used as a qualitative approach to collect information about pronunciation, with instruments in the form of modules and related documents. The steps involve collecting student responses to learning, as well as using questionnaires to understand their perceptions of the teaching and learning process of Indonesian phonetics. The ultimate goal is to provide competence to students so they can pronounce Indonesian words correctly based on phonetic symbols.